A National Representative, Cross-Sectional Study by the Hellenic Academy of NeuroImmunology (HEL.A.NI.) on COVID-19 and Multiple Sclerosis: Overall Impact and Willingness Toward Vaccination - Boziki, Marina; Styliadis, Charis; Bakirtzis, Christos; Grigoriadou, Eleni; Sintila, Aggeliki-Styliani; Nikolaidis, Ioannis; Vrienniou, Aliki; Geys, Lotte; Pelidou, Sygkliti-Henrietta; Probert, Lesley; Papazisis, Georgios; Bamidis, Panagiotis; et al. (Frontiers in Neurology, 2021)
Background: In the context of the COVID-19 pandemic, the constant needs of People with Multiple Sclerosis (PwMS) and their caregivers were urgently highlighted. Aim: The present study aims to capture the effects of the COVID-19 pandemic in several aspects of the quality of life of PwMS, in perception and behaviour in relation to COVID-19 and MS, as well as in healthcare, working conditions, and the willingness towards COVID-19 vaccination. Methods: This study is an initiative of the Hellenic Academy of Neuroimmunology (HEL.A.NI.) and it has been included in the MS Data Alliance (MSDA) Catalogue, which can be accessed after creating an account on https://msda.emif-catalogue.eu/login. Two online questionnaires were administered: i) Impact of the COVID-19 pandemic on the quality of life, the behaviour and the healthcare of PwMS (Questionnaire A) and ii) Vaccination against COVID-19 (Questionnaire B). PwMS were invited to participate by the Hellenic Federation of Persons with Multiple Sclerosis (HFoPwMS). Results: Three-hundred-ninety PwMS responded to Questionnaire A, whereas 176 PwMS provided answers for Questionnaire B. Older age, longer disease duration, and higher MS-related disability were associated with increased perceived sensitivity towards SARS-CoV-2 infection, as well as increased perceived severity of COVID-19 upon potential infection. A significant proportion of PwMS experienced restricted access to MS-related health professionals, disease-modifying therapy (DMT) prescription, and/or to MS-related laboratory examination, due to the pandemic. Subgroups of them reported exacerbated symptoms (i.e., chronic MS-related symptoms, fatigue and/or worsening of pre-existing fatigue, and sexual dysfunction and or/worsening of pre-existing sexual dysfunction). Overall, the majority of the participants reported either a strong willingness to get vaccinated against COVID-19 or a likeliness to undergo vaccination. Being aware of the HEL.A.NI. recommendations regarding COVID-19 vaccination for PwMS, was reported to increase the willingness of participants to receive the vaccine. Conclusions: Our results underline the necessity of scientific and patient organizations to take joint action to increase awareness on health-related issues during the pandemic and to provide accurate and up-to-date guidance for PwMS. Online information and communications technology (ICT) tools of polling public belief and behaviour may prove valuable as means of retaining active routes of communication between stakeholders.